A broadband magnetically coupled bistable energy harvester via parametric excitation. (15th September 2021) - Fan, Yimin; Ghayesh, Mergen H.; Lu, Tien-Fu
Highlights: A parametrically excited bistable energy harvester is firstly presented. Both initiation threshold amplitude and potential barrier have been greatly reduced. A continuously effective operational bandwidth (10–17.3 Hz) is achieved for both elements. The proposed device is applicable under a low base excitation level. Abstract: Owing to the excitation level of ambient vibrations, the wideband performance of multi-stable energy harvesters and parametrically excited energy harvesters is restricted. The bistable periodic interwell motion and parametric resonance initial threshold amplitude primarily depend on the base excitation level. In this paper, a wideband two-element piezoelectric energy harvester with both bistability and parametric resonance characteristics is presented (i.e. designed, theoretically tested, fabricated and experimentally tested) to tackle the issue of reducing the potential barrier and triggering the parametric threshold amplitude. This device is the first to utilise a directly excited element as an external oscillation source to trigger the large amplitude oscillation of a parametrically excited element through magnetic coupling effects; the periodic interwell motion revealed in the parametrically excited device infers its bistability feature; and a continuously effective operational bandwidth (10–17.3 Hz) is achieved for both elements, which infers the high-energy orbit motions. Theoretical modelling of the proposed device and the expression of the magnetic coupling effects are presented to predict the dynamics of the system, as well as verifying the experimental results. The effects of the base excitation level and the gap distance between magnets are also analysed to shed light on the flexibilities and limitations of the device.